ANALISIS ETIKA BISNIS ISLAM PADA USAHA TANI RUMPUT LAUT KECAMATAN ARUNGKEKE KABUPATEN JENEPONTO - riska, riskayanti.m; Anwar, Nurfiah; Sofyan, Syathir (Investama : Jurnal Ekonomi dan Bisnis, 2024)
This research aims to determine Islamic business ethics regarding seaweed farming in Arungkeke District, Jeneponto Regency. This type of research uses a qualitative method with a descriptive approach, the data sources used are primary data and secondary data, then the data collection methods used are observation, interviews and documentation. The instruments used in this research are the presence of the researcher, interview questions, documentation, stationery, handphone (HP). The data validity test used is data reduction, presenting the data which then draws conclusions, testing the validity of the data by triangulating the data sources. The results of this research show that the seaweed farming business in Arungkeke sub-district, Jeneponto Regency starts from the seeding and harvesting processes in accordance with Islamic business ethics, but in the next process, namely the drying and sales process, there are some farmers who commit fraud/deviations so that this has affected prices. and has violated Islamic business ethics.